Experimental study of rock breakage of an interrupted pulsed waterjet. (November 2020) - Wang, Peng; Li, Zhina; Ni, Hongjian; Liu, Yuandong; Dou, Peng
Abstract: Novel valve spring blocking structure for generating pulsed waterjet was proposed, which belonged to interrupted type and purposed using in petroleum drilling. The characteristics and rock breakage performances of the pulsed waterjet were studied through experiments by changing its structural parameters. Results showed that the pulsed waterjet could be generated through the reciprocating motion of stem under the pressure difference and its rock breakage performance was better than continuous jet under the same conditions. The theoretical frequencies were slightly higher than the experimental value due to the ignorance of friction resistance between components and viscous resistance of fluid. The results provided a basis for its applications in petroleum drilling engineering. Highlights: A valve spring blocking tool for modulating pulsed waterjet is proposed. The modulating feasibility and rock breakage of the pulsed waterjet are verified. A prototype is developed and its structural parameters are optimized.